Food Signs in Radiology - Hussain, Mehboob (Qassim University, Kingdom of Saudi Arabia, 2007)
OBJECTIVE: Certain diseases show classic radiological signs that resemble various types of food items like fruits, meat, vegetables, eggs, bakery, grocery and confectionary items. In this article various food signs are discussed and correlated with the various food items in a pictorial way. The objective of this pictorial essay is to provide the information and learn the characteristic radiological signs resembling various food items. These food signs are easy to recognize and allows a confident diagnosis on the basis of imaging findings alone or can narrow down the differential diagnosis.